Strategi Cerdas Menilai Generasi Berprestasi: Penerapan Sistem Pendukung Keputusan PROMETHEE di MTs Swasta Darularafah Raya - Sofiah Aini; Khairunnisa Ani Putri; Rika Hanifah Tanjung; Nur Sakila Ena Anjani (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The assessment of student achievement is one of the main indicators in measuring the effectiveness of the educational process in Islamic boarding schools. The assessment process that has been carried out manually tends to be subjective, so it has the potential to cause a discrepancy between the student's achievement and the results of the evaluation received. This research aims to develop a decision support system that is able to assess student achievement in an objective, measurable, and transparent manner by applying the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) method. This method is used because it has the ability to manage various assessment criteria simultaneously to produce fair and rational alternative rankings. The research approach used is quantitative descriptive by involving a number of students as research samples. The data was analyzed through the stages of determining weight, calculating preference values, and determining the values of leaving flow, entering flow, and net flow as the basis for determining the final ranking. The results of the study show that the PROMETHEE method can provide consistent and accurate ranking results, by placing students who have academic excellence, discipline, and positive personalities in the top position. These findings prove that the PROMETHEE method is effective in overcoming the subjectivity of the assessment and increasing the transparency of the evaluation process. Practically, the resulting system can help the pesantren in determining outstanding students more efficiently and based on data, as well as theoretically strengthen the application of multicriteria decision-making methods in the context of Islamic education.’